Appraising the legal position of parents under the qiṣāṣ law: immunity or a waiver - Awang Hamat, Mohd Afandi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2018)
Islam always enjoins the believer to be their brother’s keeper. They should protect, respect, and preserve the honor and integrity of their fellow human beings. The religion does not allow any harm to be inflicted upon any person without following the due process of the law. Islam considers the concept of rendering “justice for all” as a very significant element in its criminal justice system. Thus, the Islamic law of crimes and torts (jinayat) spares no expense and defines all the crimes and as well as their prescribed punishments. The law punishes offenders equally regardless of their biological status, sex, affiliation, or background. However, in some circumstances, the law mitigates punishments in favor of specific people without exonerating them in toto from liability. Mitigation of punishment in Islām therefore, cannot be seen as a grant of immunity since the main objective of the law is to maintain justice amongst all. In recent times, many people hide under the guise of the law in order to take advantage of their actions. Many cases of murder and grievous bodily injuries were alleged to have committed by persons whose responsibilities were to provide protection to their murdered or injured victims. Parents are known to be producers and protectors of their progeny, but quite number of them nowadays are alleged to have committed or aided or abetted the crimes of murder or infliction of bodily harm against their progeny. Hence, this fact cannot be detached from the misconception that is deeply involved in demarcating between “immunity” and “a waiver” under the law of Qisas. It is based on this fact that the paper examines the position of parents vis-a-vis the law of Qiṣāṣ with a view to differentiate the concept of “waiver” from that of “immunity”.